Exploration of Need and Collaboration of Technical and Vocational Education in Conventional Schools with Technical Institutions at Secondary Level - Author, Tahira Bibi, Neelam Yaqoob, Malik Omer Mansoor (JCTE, 2024)
The objectives of the research were to study the existing situation of technical education in conventional schools, which helped in assessing the need for introduction of technical education in mainstream education system. Study focused on identification of main discrepancies in existing conventional secondary education system which are causing hindrance in the effective incorporation of technical education. Study also explored the possibility of collaboration between conventional and technical institutes for technical education at secondary level. Qualitative descriptive research was conducted through the support of documentary analysis and administration of structured interview and semi-structured interview. Population for the study was ninety-seven secondary schools of Islamabad and government technical institute. Qualitative content analysis technique was applied to analyse the collected data in thematic manner, it was found that there has been need for the introduction of technical education in main stream educational system. Some of the major problems in existing system of education are deficiency of technically advanced infrastructure and other resources, mismanagement of funds and resources, non-availability of qualified technical teachers, fixed mindset of society, gaps in planning and implementation stages etc. It was also evident from the study that there exists intense possibility of collaboration between technical institutes and conventional secondary schools for incorporation of technical education. *Lecturer, Allama Iqbal Open University Islamabad. Email: tahira.naushahi@aiou.edu.pk **M.Phil Scholar, Allama Iqbal Open University Islamabad. Email: canvassanalysis@gmail.com ***Student, Allama Iqbal Open University Islamabad. Email: canvassanalysis@gmail.com